Volume 3: Coal, Biomass and Alternative Fuels; Cycle Innovations; Electric Power; Industrial and Cogeneration Applications; Org 2017
DOI: 10.1115/gt2017-64341
|View full text |Cite
|
Sign up to set email alerts
|

Parallel Between Rankine and Combined-Cycle Power Plants Configurations Burning Blast Furnace Gas

Abstract: The increasing fuel prices and stringent environmental legislation compel industries worldwide to pursue means to increase their processes efficiency. A higher efficiency relates to a reduction in fuel consumption, which results in a lower operational cost and emissions. When considering a steel mill, processes encountered in the blast furnace and in the coke oven, for example, generate gases that can be availed as low-grade fuels to return some sort of energy back to the process. This practice reduces the amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Many studies have been conducted to improve the operating performance of BFGCCs. Campos et al [12] compared the operating performance of a BFGCC and the Rankine cycle. The results showed that the combined-cycle plant exhibited higher efficiency, rated power, and flexibility but with a higher cost and operational complexity.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have been conducted to improve the operating performance of BFGCCs. Campos et al [12] compared the operating performance of a BFGCC and the Rankine cycle. The results showed that the combined-cycle plant exhibited higher efficiency, rated power, and flexibility but with a higher cost and operational complexity.…”
Section: Introductionmentioning
confidence: 99%
“…Campos [2] reported an exergy-based comparison between BFG-fueled combined cycle plants and steam cycle plant configurations, providing a method of direct combustion of blast furnace gas for power generation. Campos [3] compared the efficiency of combined cycle and Rankine cycle in BFG utilization, showing that the combined cycle has higher power generation efficiency. Ryzhkov [4] discussed the worldwide practice of operating combined cycle power plants on BFG to date, and the principles of upgrading a standard gas turbine power plant to a combustion BFG were studied.…”
Section: Introductionmentioning
confidence: 99%